Citizens without Nations – a Clarification - Prak, Maarten (TSEG - The Low Countries Journal of Social and Economic History, 2020)
My book Citizens without Nations might be read as a triple provocation, as it challenges three received wisdoms of historical textbooks. The first, and perhaps most fundamental, is the idea that the grand narratives of the past have to be the histories of nations and their states.